Thiophene‐2, 3‐Dialdehyde Enables Chemoselective Cyclization on Unprotected Peptides, Proteins, and Phage Displayed Peptides. Issue 11 (26th September 2022) - Wei, Tongyao; Li, Dongfang; Zhang, Yue; Tang, Yubo; Zhou, Haiyan; Liu, Han; Li, Xuechen
Abstract: Ortho ‐phthalaldehyde has recently found wide potentials for protein bioconjugation and peptide cyclization. Herein, the second‐generation dialdehyde‐based peptide cyclization method is reported. The thiophene‐2, 3‐dialdehyde (TDA) reacts specifically with the primary amine (from Lys side chain or peptide N‐terminus) and thiol (from Cys side chain) within unprotected peptides to generate a highly stable thieno[2, 3‐ c ]pyrrole‐bridged cyclic structure, while it does not react with primary amine alone. This reaction is carried out in the aqueous buffer and features tolerance of diverse functionalities, rapid and clean transformation, and operational simplicity. The features allow TDA to be used for protein stapling and phage displayed peptide cyclization. Abstract : The thiophene‐2, 3‐dialdehyde (TDA) facilitated cyclization of unprotected native peptides has been developed. Compared with the reaction mediated by o ‐phthalaldehyde, TDA shows better selectivity for S – N cyclization over the N ‐modification, which makes TDA suitable for the cyclization of proteins and phage displayed peptides.